Oral Health Maintenance In Children With Self Brushing And Parents Guidence: A Pilot Study - AISHWARY.A.S,; DR.DEEPA GURUNATHAN, (International Journal of Pharma and Bio Sciences, 2015)
Behavioural habits are mostly thought at home, which also includes brushing. Brushing is very important for maintaining oral hygiene. It is very important to evaluate the children their brushing habit. Parents play a main role in guiding them. Our aim is to access the tooth brushing habits of children and to determine the role of supervision given to them by the parents. This analysis is to create awareness about brushing to the parents to self evaluate if they are guiding their children properly. A self- designed questionnaire was used to collect Information from parents of 150 primary children in Chennai. Statistical analysis was done using SPSS 16.0 version. Tooth brushing was started at the mean age of 48 months. 77.7% of the children used tooth paste and tooth brush for cleaning teeth and brushing habits were mainly introduced 96% by mothers. 32.7% of children were cooperative when they introduced brushing. Once brushing was found to be common. Well educated parents had confidence on their teaching the habit. The lack of knowledege regarding the initiation of brushing and the frequency of brushing might lead to inadequate oral hygiene. Hence. promoting knowledge to parents could improve the children oral health status.